2014
DOI: 10.1007/s11356-014-3558-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of Eichhornia crassipes exposed to Cr (III)

Abstract: The effect of exposure of Eichhornia crassipes to Cr (III) was assessed by measuring changes in photosynthetic pigments, malondialdehyde, superoxide dismutase, glutathione reductase, catalase, and guaiacol peroxidase activities, as well as Cr concentration in tissues. Cr concentration in roots was significantly higher than in aerial parts and increased with Cr concentration in water. Photosynthetic pigments increased significantly, whereas the activities of antioxidant enzymes varied differently in plant tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Conversely, González et al [11] observed a decrease in the chlorophyll content and PSII performance in barley plants, which simultaneously showed an increase in growth that was caused by Cd treatment. Generally, the stimulation of growth by Cd is positively correlated with a significant decrease in the total chlorophyll content and activity of the photosystems [11,43]. The results presented in this paper also confirmed this relationship, which may additionally prove the high toxic effect of Cd on these parameters (Figures 3a, 4 and 6a).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Conversely, González et al [11] observed a decrease in the chlorophyll content and PSII performance in barley plants, which simultaneously showed an increase in growth that was caused by Cd treatment. Generally, the stimulation of growth by Cd is positively correlated with a significant decrease in the total chlorophyll content and activity of the photosystems [11,43]. The results presented in this paper also confirmed this relationship, which may additionally prove the high toxic effect of Cd on these parameters (Figures 3a, 4 and 6a).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, improvements in the content of photosynthetic and accessory pigments (such as chlorophyll a, chlorophyll b, total chlorophyll and/or carotenoids) were observed in the leaves of different plant species after Cd exposure [4]. Conversely, González et al [11] observed a decrease in the chlorophyll content and PSII performance in barley plants, which simultaneously showed an increase in growth that was caused by Cd treatment. Generally, the stimulation of growth by Cd is positively correlated with a significant decrease in the total chlorophyll content and activity of the photosystems [11,43].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This effect was also caused by As in the case of Spirodela polyrrhiza L. [ 65 ]. Besides, numerous experiments with chromium (Cr) revealed hormetic growth in the cases of Eichhornia crassipes [ 67 ], Salsola kali L. [ 68 ], Lemna minuta [ 69 ], Allium cepa L. [ 70 ] and Capsicium annum L. [ 71 ]. An hormetic response was observed as well, in the case of elements such as lanthanum (La) for Lonicera japonica [ 72 ], Oryza sativa L. [ 73 ] and Arabis paniculata [ 66 ], Pb for Pisum sativum [ 35 ], Brassica pekinensis [ 74 ] and Dianthus carthusianorum [ 60 ], Hg for Anthyllis vulneraria [ 75 ] and Helianthus tuberosus [ 76 ], palladium (Pd) for P. sativum L. [ 77 ], platinum (Pt) for Arabidopsis thaliana [ 78 ], uranium (U) for Schizachyrium scoparium [ 79 ], Zn for Thlaspi caerulescens [ 80 ], Sedum alfredii [ 57 ] and Arabis paniculata [ 66 ].…”
Section: Hormesis As a Biological Phenomenon In The Context Of Orgmentioning
confidence: 99%
“…In this context, it has been assumed that Cr(III) at low concentrations can be beneficial to plants, although it is highly toxic at high concentrations (Singh et al ). However, increasing evidence indicates that Cr(III) causes more toxic than beneficial effects on both aquatic and terrestrial plants (Karuppanapandian and Kumariah ; González et al ; Lukina et al ). Even in some lower and higher plants, such as Pseudokirchneriella subcapitata , Chlorella kessleri , and Salsola kali , Cr(III) seems to be more toxic than Cr(VI) (Gardea‐Torresdey et al ; Vignati et al ).…”
Section: Introductionmentioning
confidence: 99%